Determination of the quality of stripe-marked and cracked eggs during storage - Liu, Yu Chi; Chen, Ter Hsin; Wu, Ying Chen; Tan, Fa Jui (Animal bioscience, 2017)
Stripe marks, which occasionally occur on the shell, do not cause breakage to the shell and shell membranes of eggs. This study investigated the quality of intact eggs (IEs), minor stripe-marked eggs (MEs), severe stripe-marked eggs (SEs), and cracked eggs (CEs) during 3-week storage at 25°C. Shell eggs were collected the day after being laid and were washed. Among them, eggs without any visual cracks or stripe marks on the shells were evaluated as IEs by the plant employees using candling in a darkened egg storage room; the remaining eggs exhibited some eggshell defects. At day 3, the eggs were further categorized into IEs, MEs, SEs, CEs, and broken eggs (BEs) on the basis of the description given. Except BEs, which were discarded, the remaining eggs were stored at 25°C (approximate relative humidity 50%) and then analyzed. Stripe marks were observed primarily within the first 3 days after washing. At day 3, CEs had significantly (p<0.05) lower Haugh unit values, but all eggs had grades AA or A, according to the United States Department of Agriculture standard. As storage time increased, differences in egg quality between groups were more obvious. IEs had the highest eggshell breaking strength. During storage, the total plate counts and pathogens, namely , spp., , and spp., were not detectable in the internal content of IEs and SEs. In conclusion, cracks degraded egg quality severely and minor stripe marks only slightly influenced the egg quality.